EFFICIENT TRACTION AND EXTERNAL RESISTANCE OF AIRCRAFT POWER PLANT - Юрий Юрьевич Терещенко; Иван Алексеевич Ластивка; Павел Владимирович Гуменюк; Су Хунсян (Авіаційно-космічна техніка та технологія, 2020)
Increasing the efficiency and effectiveness of a gas turbine engine can be achieved through a comprehensive review of all tasks that determine the parameters and characteristics of an aircraft power plant and aircraft. An important place in this complex is occupied by the problem of obtaining the most efficient traction and power plant based on the integration of the parameters and characteristics of the nacelle and gas turbine engine, consisting of a universal gas generator module and a turbofan module. Reducing the negative impact of the engine nacelle module on effective traction and effective specific fuel consumption is an urgent problem that can be solved based on the results of studies of the integration parameters and characteristics of the engine nacelle of the gas generator module and the gas turbine engine with the turbine-fan extension module, namely, with the implementation of structurally layout diagram of a gas turbine engine with a modular design with a rear arrangement of a turbofan attachment. For modern power plants with bypass gas turbine engines with a large bypass ratio, the external resistance is 2-3 % of the engine thrust during cruising operation. The results of experimental studies have shown that the external resistance of power plants with bypass gas turbine engines of modern supersonic aircraft is 4-6 % of the engine thrust during cruising operation. The paper considers the issues of aerodynamic integration of a gas turbine engine and a nacelle of an aircraft power plant. Aerothermogasdynamic integration of a gas turbine engine and an aircraft provides for the coordination of the parameters of the working process and the characteristics of the gas turbine engine and the parameters and characteristics of the nacelle of the aircraft in order to obtain optimal parameters and characteristics of the aircraft in the design flight conditions. The dependences of the relative effective thrust on the flight velocity are obtained. The obtained dependencies show the influence of the external resistance of the engine nacelle on the effective thrust of the bypass engine at subsonic flight velocities. The calculations were performed to lengthen the nacelle in the range from 4 to 8.